(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Overweight and obesity have become a public health issue in Mexico. Among actions taken by the authorities to solve it, the Norm 051 that regulates labeling of packaged food and beverages has been modified recently. This study aims to know the initial impact of warning labels on adult consumers habits, from a social marketing perspective. A quantitative design was developed and 514 consumers of 18 years on were interviewed. Major findings show that consumers are aware of warning seals on the products, but are not motivated to change their habits, nor to stop buying them. Social marketing is a discipline that can contribute to design integral campaigns to solve this problem, since the actions taken by the Mexican authorities lack of an integral approach.